Liver cirrhosis and splenomegaly associated with Schistosoma mansoni in a Sudanese woman in Malaysia : A case report - Yamuna, Rajoo; Rohela, Mahmud; Ng, Rong Xiang; Sharifah F., S. Omar; Kumar, G.; Yvonne Ai, Lian Lim; Arine Fadzlun, Ahmad; Amirah, Amir; Zurainee, Mohamed Nor; Romano, Ngui (Elsevier Science, Ltd., 2015)
We report a case of a patient with Schistosoma mansoni infection who presented with liver cirrhosis and splenomegaly. She was diagnosed by a serological test and Kato-Katz thick smear stool examination. The patient was a 52-year-old woman from Sudan who came to Malaysia for a week to visit her sons. The patient lives in the middle of Rabak region, Sudan, a highly endemic area for schistosomiasis where her daily routine includes rearing of cows and farming. The site of toilet and sources of drinking water are canals and wells; both infested with snails. Patient had a long history of exposure and coming into contact with water from these canals and wells.